The effect of hearing augmentation on cognitive assessment scores: a pilot crossover randomized controlled trial - Ibrahim, Amirah Fatin; Lim Abdullah, Khatijah; Zilany, Muhammad Shamsul Arefeen; Zaidon, Ahmad Zuhair; Ong, Siew Hui; Tan, Maw Pin (Springer Verlag, 2016)
This randomized cross-over pilot study aimed to evaluate the effect of hearing augmentation on cognitive assessment scores and duration to complete cognitive assessment among the elderly in-patients in a teaching hospital. A hearing amplifier was used for hearing augmentation and the Montreal Cognitive Assessment (MoCA) test was used to assess cognition. Seventy one patients were allocated into Group A (n=33) or Group B (n=38) using block randomization. There was no significant difference in total MoCA scores with and without hearing augmentation (p = 0.622). There was a significant improvement in the total scores on the second test that suggests a learning effect (p < 0.05). There was also no significant difference in time taken to complete cognitive assessment with and without hearing augmentation (p = 0.879). Similar statistical tests performed on a subgroup of patients with hearing impairment did not reveal significant results. The results of this study will now inform a larger randomized controlled study evaluating the use of hearing amplifiers as cost-effective solutions to hearing impairment in our older population.